Physiological and biochemical dynamics of black gram (Vigna mungo L.) genotypes under high temperature stress at pod formation stage - Pavithra, N; Jayalalitha, K; Sujatha, T; Harisatyanarayana, N; Jyothi, L N; Roja, V (Plant Science Today, 2026)
Blackgram is one of the important short-duration pulse crop which is sensitive to high temperatures. The rising global temperatures are threatening the yield of blackgram by altering the physiological and biochemical processes at the cellular level. Keeping this in view, the present investigation was carried out for a better understanding of genotypic variability and the physiological and biochemical mechanisms governing heat stress tolerance, which can help in identifying heat-tolerant blackgram genotypes that can yield better under climate change scenarios. Thirty blackgram genotypes were evaluated for high temperature stress tolerance during summer 2022 and 2023 at College Farm, Agricultural College, Bapatla, Acharya N.G Ranga Agricultural University. All the observations were recorded at the pod formation stage and analysed statistically. The results showed that the genotypes TBG-129, LBG-1015, PU-1804 and PU-31 were found to withstand high temperatures by maintaining higher chlorophyll stability index, cooler canopies, more proline accumulation and higher antioxidant defence activity, reflecting the lesser membrane leakage due to decrease in free radicals and MDA accumulation, thereby recording higher seed yield compared to other genotypes. The PCA results revealed considerable variability among the traits, accounting for 81.37 % of total variability. The blackgram genotypes TBG-129, LBG-1015, PU-1804 and PU-31 can be used as donors in the breeding programme for the development of thermotolerant genotypes.